Factors that contribute to students’ reluctance in learning / Zulkifly Abdullah - Abdullah, Zulkifly (2002)
Discipline is a simple word yet it has many shades of meaning. Discipline can also be defined as a quality or a state of behavior in a person or in a group of people Discipline can also mean a process or an effort to bring about obedience and order. This is reflected in our efforts to discipline ourselves from young. Schools in Malaysia seemed to be experiencing an increase in indisciplined behavior. In schools, discipline is essential because teachers teach students and not subjects. They are moulding the future citizens. Therefore, the responsibility is to orientate them towards desirable norms and values. A Malay proverb states that should we want the bamboo to be straight and supple, then we must shape it when it is still a shoot. In Malaysia, when we say we need disciplined citizens, in a disciplined society, we mean people who observe social norms, obey rules and regulations and uphold the national constitution so that the society remains united and cohesive always. Also we need disciplined citizens because we need a workforce that is productive, responsible and conscious of the need to work hard to bring about prosperity and wealth to the country’s economy and social well-being. The school is a microcosm of society. The disciplining process begins there. Discipline is an essential process in the classroom because without it the process of education cannot take place. There is a need for order, regimentation and routine in schools before teaching and learning can take place.